Model Pendidikan Karakter Berbasis Nilai-Nilai Tradisi Pesantren - Saipullah, Saipullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
Now, there are acts of discrimination against Islamic boarding schools, where it is stated that Islamic boarding schools are referred to as places where radical understanding grows and rejects the progress of the digital world. Luckily, it is contrary to the facts in the field which were proven from direct pre-survey in Riyadlatul Ulum Islamic boarding school at Bumiharjo 39 B Batanghari East Lampung. This research aims to discover character education models based on the values of Islamic boarding school tradition. This research employed a qualitative phenomenological approach. Data is collected by natural setting as a live data source. The result of this research showed that the traditional values practiced at Riyadlatul Ulum Islamic boarding school are responsibility, sincerity, hard work, smart, clean, religious, nationalism, deliberation and award value. Moreover, the educational characteristic model developed at Riyadlatul Ulum Islamic boarding school is information supply (ma’lumat tsabiqoh) related to the nobel character through book study in order to grow sensitivity and realization of goodness through tradition that were implemented for a 6 years study program. The findings of this study prove that negative opinions about Islamic boarding schools cannot be generalized as a whole because Pesantren actually contribute to the development of good education characteristics.